2020
DOI: 10.3389/fpubh.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

New Epidemiological, Clinical and Economic Data for Patients With Acromegaly in Bulgaria

Abstract: Background: Acromegaly and its comorbidities affect the patients' quality of life, each healthcare system and the society. This study aimed to evaluate clinical characteristics and treatment patterns and the economic burden of acromegaly.Materials and methods: All patients with acromegaly treated with expensive medicines and regularly followed up at the main expert clinical center for acromegaly in the country were included in this nationwide, retrospective, observational, population-based study. Patient chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 37 publications
6
21
2
1
Order By: Relevance
“…The female sex was correlated with a diagnostic delay and more comorbidities at follow-up, consistent with previous results (8,19,27,29). The average age of patients was 39 years, approximately 10 years younger than the patients from Sweden, France, Denmark and the United States but close to those from Korea and Bulgaria (14,15,23,(30)(31)(32). We showed that older age was suggested to be correlated with more comorbidities, in accordance with published literature (33,34).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The female sex was correlated with a diagnostic delay and more comorbidities at follow-up, consistent with previous results (8,19,27,29). The average age of patients was 39 years, approximately 10 years younger than the patients from Sweden, France, Denmark and the United States but close to those from Korea and Bulgaria (14,15,23,(30)(31)(32). We showed that older age was suggested to be correlated with more comorbidities, in accordance with published literature (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…Acromegaly affects both males and females; many studies have demonstrated that females are more frequently affected, but some have indicated that both sexes are equally affected (9,14,15,17,18,21,22,(27)(28)(29). In the present study, females accounted for 58.8% of all patients, significantly larger than the percentage of males.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations